DIFFERENCES IN GAME-RELATED STATISTICS BETWEEN WINNING AND LOSING TEAMS IN NCAA DIVISION-II MEN'S BASKETBALL - Dimitrije Cabarkapa; Michael A. Deane; Damjana V. Cabarkapa; Grant T. Jones; Andrew C. Fry (Scientific Publishing House. NSA Press, 2022)
Knowing how to design training regimens and modify offensive and defensive strategies to accurately resemble on-court competitive demands can help the team secure the winning game outcome. Thus, the purpose of the present study was to examine differences in game-related statistics between winning and losing teams at the National Collegiate Athletic Association (NCAA) Division-II level of men's basketball competition and determine which performance parameters have the greatest impact in differentiating between winning and losing game outcomes. The data scraping technique was used to obtain publicly available box scores during the 2018-19 competitive season. The total number of games examined in the present investigation was 4630. The findings of the present study indicate that winning teams: a) made more field-goal and three-point shots; b) attempted and made more free-throw shots; c) attained superior free-throw, two-point, and three-point shooting efficiency; d) accumulated more assists, steals, blocks, and offensive, defensive, and total rebounds; e) had fewer turnovers and personal fouls. Moreover, field-goal percentage, defensive rebounds, and assists showed to be the top three game-related statistics capable of discriminating winning from losing game outcomes on the NCAA Division-II level of competition, accounting for 17.0%, 12.7%, and 12.6% of the total percentage of the explained variance, respectively.